Influence of personal and environmental factors on psychological well-being of students with hearing impairment in Ibadan, Oyo State (2018)
The poor state of the psychological well-being of students with hearing impairment has been worrisome to researchers, teachers, parents and students with hearing impairment over the years. Hence, this study examined influence of personal and environmental factors (Parental involvement and social support) on psychological well-being of students with hearing impairment. The descriptive research design of the correlational type was adopted. Purposive sampling technique was used to select 100 students with hearing impairment from three senior secondary schools in Ibadan, Oyo State, Nigeria. Data were collected with: Personality Questionnaire (r = 0.87), Parental Involvement Questionnaire (r =.0.79), Social Support Scale (r = 0.82) and Ryff Psychological Wellbeing Scale (r = 0.85). Data were analysed using Pearson product moment correlation and Multiple regressions at 0.05 level of significance. The results showed that:. Personality (r = . 727), Parental Involvement (r = .446) and Social Support (r = .806) positively correlated with psychological well-being. Personality, parental involvement, and social support jointly contributed to psychological well-being of students with hearing impairment. The relative contributions of the independent variables to psychological well-being were as follows; personality ([I = 0.622, t-7/377), parental involvement (/3 = 0.205, t=4.093) and social support (ft - 0.622, t-12.161). Personality, supportive parental involvement and positive social support are important determinants of psychological wellbeing of students with hearing impairment in Ibadan, Oyo State, Nigeria. Parents, teachers and members of the community where students with hearing impairment live, should make the environment friendly in order to help boost their psychological wellbeing.